2016
DOI: 10.1097/pas.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Prognostic Value of BAP1 Mutation Pattern, Chromosome 3 Status, and BAP1 Immunohistochemistry in Uveal Melanoma

Abstract: Uveal melanoma (UM), a tumor of the eye, can be divided into 2 major classes correlating with patients' prognosis. Gene expression profiles and chromosome 3 status are correlated with tumor classification and prognosis. Somatic BAP1 mutations are another feature largely restricted to metastatic UM. Here we performed thorough BAP1 mutation analysis including sequencing and gene dosage analysis of all BAP1 coding exons as well as methylation analysis of the promoter CpG island in a set of 66 UMs. The results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
83
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 24 publications
12
83
0
3
Order By: Relevance
“…In the current study, this included tumours resected because of size, location, recurrence, secondary complications, and patient preference. Whilst we recognize that there may be a potential bias as compared with an analysis of all UM, the frequency of nBAP1 negativity in this study (54%) is consistent with that reported in the literature (43–58%) 23, 38, 39. Similar to these other reports, we demonstrated a correlation between loss of nBAP1 expression and poor prognostic parameters known to be associated with ‘high risk’ UM – i.e.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, this included tumours resected because of size, location, recurrence, secondary complications, and patient preference. Whilst we recognize that there may be a potential bias as compared with an analysis of all UM, the frequency of nBAP1 negativity in this study (54%) is consistent with that reported in the literature (43–58%) 23, 38, 39. Similar to these other reports, we demonstrated a correlation between loss of nBAP1 expression and poor prognostic parameters known to be associated with ‘high risk’ UM – i.e.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Van de Nes et al demonstrated in a cohort of 66 UM that 33/37 (89%) M3 UM had a BAP1 mutation together with an absence of nBAP1 protein expression 23. A similar proportion was reported by Koopmans et al in their study of 74 UM, with 88% of the M3 UM harbouring a BAP1 mutation together with loss of nuclear protein expression 39.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations